Low-Risk Anomaly : Evidence from the Nordic equity markets - Hartikainen, Eetu (My University, 2024)
This study seeks to examine the low-risk anomaly in Nordic equity markets from February 2005 to March 2024. While the low-risk anomaly has been a subject of extensive research, particularly in US markets, it remains under-researched in the Nordic context. To address this gap, this study aims to provide a comprehensive analysis of the anomaly within the Nordic region. Given the absence of standardized methodologies for analyzing the low-risk anomaly, this study investigates the efficacy of various approaches to exploit this phenomenon. Specifically, portfolios sorted by volatility, beta, and idiosyncratic volatility are analyzed, utilizing rolling risk measurement periods of 36, 24, and 12 months. Furthermore, this study assesses the robustness of the low-risk anomaly across different market capitalizations, namely large-cap and small-cap stocks. It also evaluates the persistence of the anomaly over holding periods exceeding the standard one-month duration. The findings confirm the presence of a low-risk anomaly in Nordic equity markets. Low-risk portfolios consistently outperform high-risk portfolios, generating superior raw excess returns and risk-adjusted returns. All long-short portfolios tested across various methodologies produced statistically significant FF5 alphas, with the majority also yielding significant FF6 alphas. Strongest results were driven by idiosyncratic volatility sorted portfolios whereas beta sorted portfolios generated weakest results. Additionally, 36-month sorted portfolios generated the most pronounced differences between lowest and highest risk portfolios, whereas 12- month sorted portfolios generated the least pronounced differences. Furthermore, the low-risk anomaly is more driven by the short leg than the long leg. Results for large cap stocks were mixed, as the return spreads between low-risk and high-risk portfolio were more muted and only idiosyncratic volatility sorted portfolios generated statistically significant FF5 alpha. Furthermore, low-risk anomaly is robust to longer holding periods (up to 12 months). Tämä tutkimus tarkastelee alhaisen riskin anomaliaa Pohjoismaisilla osakemarkkinoilla helmikuusta 2005 maaliskuuhun 2024. Vaikka ilmiötä on tutkittu laajasti erityisesti Yhdysvalloissa, Pohjoismaissa aiheeseen liittyvä tutkimus on ollut rajallista. Koska alhaisen riskin anomalian mittaamiseen ei ole yhtä yleisesti hyväksyttyä menetelmää, tässä tutkimuksessa vertaillaan erilaisia mittausmenetelmiä niiden eroavaisuuksien selvittämiseksi. Anomalian esiintyvyyttä arvioidaan mittaamalla riskiä volatiliteetin, betan ja idiosynkraattisen volatiliteetin avulla, käyttäen eripituisia riskin mittausjaksoja. Lisäksi tutkimuksessa tarkastellaan anomalian esiintyvyyttä suurissa ja pienissä osakkeissa sekä pitoajoilla, jotka ovat pidempiä kuin tavanomainen yhden kuukauden jakso. Tämä tutkielma osoittaa alhaisen riskin anomalian esiintyvyyden Pohjoismaisilla osakemarkkinoilla. Tutkimuksen tulokset osoittavat, että matalariskiset osakkeet tuottavat paremmin kuin korkeariskiset osakkeet. Kaikki eri menetelmillä muodostetut "long-short"- portfoliot saavuttivat positiivisen ja tilastollisesti merkitsevän FF5 alphan, ja lähes kaikki saavuttivat myös tilastollisesti merkitsevän FF6 alphan. Suurimmat tuottoerot matalariskisten ja korkeariskisten osakkeiden välillä havaitaan, kun riski määritellään idiosynkraattisen volatiliteetin perusteella, kun taas pienimmät erot ilmenevät betan perusteella määritellyssä riskissä. Lisäksi tuottoerot korostuvat eniten, kun osakkeet jaotellaan 36 kuukauden riskin perusteella, ja pienimmät erot syntyvät, kun jaottelu tehdään 12 kuukauden riskin perusteella. Tulokset osoittavat, että alhaisen riskin anomalia johtuu enemmän korkeariskisten osakkeiden alituotosta kuin matalariskisten osakkeiden ylituotosta. Suurten osakkeiden osalta tulokset olivat ristiriitaisia, sillä tuottoero matalariskisten ja korkeariskisten osakkeiden välillä kaventui merkittävästi, ja ainoastaan idiosynkraattisen volatiliteetin perusteella jaoteltu portfolio tuotti tilastollisesti merkitsevän FF5 alphan. Lisäksi tutkimus osoittaa, että alhaisen riskin anomalia esiintyy myös pidemmillä, jopa 12 kuukauden, pitoajoilla.
Keywords: fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance